Aerobic Endurance Capacity (Vo₂Max) Using Bleep Test on Students of Pjkr Study Programme - Atty, Jimmy Charter; Rohi, Isak Riwu; Nafie, Agustinnus J.; Mae, Ramona M.; Lika, James Klemen (Universitas PGRI Palembang, 2024)
The aerobic endurance capacity of PJKR progdi students must be above the average of the aerobic endurance capacity of other students. Observing this phenomenon, this study aims to determine the capacity of aerobic endurance (VO₂Max) using the Bleep Test in first semester students of the PJKR study programme. The method in this study is quantitative non-experimental with a quantitative descriptive approach. The population used in this study were first semester students of the PJKR study programme, the number of samples was 70 people. The research was carried out at the PJKR study programme. Data analysis using statistical analysis includes preparation, tabulation and data application. Based on the results of research and discussion, it is concluded that the level of physical fitness of Physical Education study programme students is categorised as very less (95.51%) and 4.28% of students are categorised as less. It can be said that more than 95% of physical education study programme students have a very poor level of physical fitness. Students need to manage their diet, rest and exercise activities regularly. The study programme is recommended to monitor and improve physical fitness for students through training and evaluation programmes.